Teacher Feedback and Student Writing Improvement in EFL Classrooms: A Longitudinal Study - Hafidhoh, Husnul; Agus, Cecep (Politeknik Siber Cerdika Internasional, 2025)
In English as a Foreign Language (EFL) contexts, teacher feedback plays a pivotal role in facilitating students' writing development. However, limited longitudinal research has explored how sustained feedback practices influence student improvement over time. This study aims to investigate the impact of teacher feedback on students' writing performance in EFL classrooms, focusing on the progression of writing skills across an academic year. Employing a longitudinal research design, this study followed 60 EFL students from a secondary school in Indonesia over two semesters. Data were collected through students' writing samples, teacher feedback forms, and semi-structured interviews. A mixed-method approach was used: quantitative data were analyzed using repeated-measures ANOVA to assess changes in writing scores, while qualitative data from interviews were coded thematically to explore students' perceptions of feedback. Findings indicated a statistically significant improvement in students' writing performance over time, particularly in coherence, vocabulary usage, and grammatical accuracy. Students reported that timely, specific, and formative feedback contributed positively to their writing development. Furthermore, teacher feedback that was dialogic in nature (i.e., allowing for student response and reflection) had a more substantial impact compared to solely corrective feedback.